If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 64 = -6z + 10 Reorder the terms: 64 = 10 + -6z Solving 64 = 10 + -6z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '6z' to each side of the equation. 64 + 6z = 10 + -6z + 6z Combine like terms: -6z + 6z = 0 64 + 6z = 10 + 0 64 + 6z = 10 Add '-64' to each side of the equation. 64 + -64 + 6z = 10 + -64 Combine like terms: 64 + -64 = 0 0 + 6z = 10 + -64 6z = 10 + -64 Combine like terms: 10 + -64 = -54 6z = -54 Divide each side by '6'. z = -9 Simplifying z = -9
| (x-1)/x=0,25 | | 2x-4+14=180 | | 40x+20y+65= | | n=80 | | 5z+2=4p-1 | | y=8+4(h-1) | | 3z-1=6z+20 | | 6x+5=91-x | | 26=5(x+4)-7x | | 9x+7=38+6x-4 | | -5x+4y=-8 | | 8g+15=5g | | 2x^2-6x=55 | | Y=x^2-18x+80 | | 3(1-2x)-9=2(x+5) | | 242=x^2 | | 0.37x+9.436=0.81x+6.708 | | 8=-2(x-7) | | 20=5/6y | | 1/3(x+3)=5+(4x/3) | | 3x+3=43 | | 6x+7+-2x+4=4(-3x-5)-17 | | 8x-17=3x+3(15y-30) | | 8(y-1)-x(y-1)=0 | | (2y+11)=(4y-3) | | 25-7x=7-4x | | 4(y+2)=-12 | | 1-6k=11-4k | | X*125=Y | | 8p-1=3p+3 | | 151=5x+8+9x+3 | | -9q=-4-9q |